Prototype Survey of Path Planning and Obstacle Avoidance in UAV Systems - SARATH CHANDRA, S; A. S. C. S. SASTRY, Dr (International Journal of Engineering and Technology, 2018)
In recent years, have seen rapidly growing interest with implementation and development of different type of networks of multiple unnamed aerial vehicles (UAV), as aerial sensor networks for inter co-operative monitoring, surveillance monitoring and rapid emergency response for communication. This is an emerging concept in real time communicative networks. Path detection, planning and obstacle avoidance is the aggressive representation for unnamed aerial vehicles in indoor environments. There are many techniques/approaches are introduced to evaluate above features for real time communicative environments. So in this paper, we discuss about those techniques implementation procedure and brief description regarding obstacle avoidance, multi-point interaction to track the location in wireless network communications. This paper analysis most successful path detection, planning and other reference based methods with successive description in real time scenario. Furthermore, a comprehensive with comparable result analysis of each path planning technique by considering their implementation in time complexityÂ and other parameters in real time communicative networks. Â